Implementasi Pembelajaran Berbasis Proyek dalam Materi Ekologi untuk Meningkatkan Keterampilan Berpikir Kritis Siswa - Sekar Arum; Ayu Prameswari (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to examine the effect of project-based learning on students' critical thinking skills in studying ecology. The background of this study is the need for innovative learning methods that can improve students' analytical skills in understanding ecological concepts. The method used is experimental research with a pretest-posttest design. Data were collected through observation and critical thinking skills tests before and after learning. The results showed a significant increase in students' critical thinking skills after the implementation of project-based learning. These findings indicate that project-based learning can be an effective strategy in improving students' critical thinking skills in biology education.